KONFLIK BATIN TOKOH UTAMA DALAM NOVEL STRONG GIRL KARYA DINA AMELIA SERTA IMPLIKASINYA DALAM PEMBELAJARAN SASTRA DI SMA - Servina Anindhita; Nani Solihati (Universitas Negeri Makassar, 2023)
The purpose of this study is to identify the inner conflict of Adel's character in the novel Strong Girl by Dina Amelia by using Saludin Muis's theory, which discusses the types of inner conflicts and the implications of literature in high school, to identify and evaluate the implications of learning literature based on the novel Strong Girl by Dina Amelia. This research uses the descriptive qualitative method, where the material or data is descriptive. The results of the data analysis found 12 types of internal conflict using Saludin Muis' theory in the novel Strong Girl by Dina Amelia. The novel Strong Girl by Dina Amelia focuses more on the psychological side of Adel's character because Alen, Adel's mother, has regretted raising a child like Adel, and in some events, Adel often gets verbal and physical violence from her mother.